The Effects of Local Alendronate with Biphasic Calcium Phosphate on Augmented Rabbit Sinus - Zainab M. Hameed (Journal of Global Pharma Technology, 2016)
Background: Biphasic calcium phosphate   considered a good synthetic bone graft substitutes, and its effective role in sinus floor lifting. Alendronate (ALN) is a common formula of bisphosphonates that have potential effects to decrease the osteoclast differentiation. Aim of  study is -to evaluate histologic and histomorphometric effect of  local alendronate with  BCP  with  ratio( 30: 70)when used with  a  rabbit sinus. Materials and Methods:--8 male adult (New Zeeland) rabbits were selected. Sixsteen sinus floor, elevation procedures, were prepared, 2 on each animal and were distributed into two groups (n=4): the BCP group, where the sinus was grafted with, B CP with HA ׃β ̵ TCP (30 ׃70).And BCP/ALN group, where the sinus grafted with (OSTEON II), mixed with Alendronate solution, the solution was prepared by dissolving of 20 mg of ALN with 1 ml of distal water. The rabbits killed at 7, 14, 30 and 60 days after surgery and the histological   analysis were achieved. The histologic evaluation was performed using a light microscope. The new bone area represents the proportion of dark red area to the total augmented area, while the (FCT) represents the proportion of light red area to the total augmented area. Results: Although there  were significant differences  of  new  bone formation between two study groups after 7,14 and 30 days  periods ,but there's  non-significant differences occurred after 60 days . In addition, the FCT area was decreased in these two groups with the progressing healing periods, at the same time the FCT area was less in BCP/AL group; and there were   statistically nonsignificant differences between two groups after 60 days periods. Conclusions: - Local application of ALN with BCP with the (HA: β ̵ TCP (30:70)) ratio, did not have beneficial effects when augmented sinus rabbit model to increase bone formation. Keywords: Biphasic calcium phosphate; Alendronate; Rabbit maxillary sinus.